Analisis Pengukuran Beban Kerja Mental pada Karyawan Bagian Produksi Menggunakan Metode NASA-TLX di PT. Riau Graindo - Satriardi, Satriardi; Nurhamzah, Agas; Ananda Yul, Faradila (Fakultas Teknik UMRI, 2026)
PT. Riau Graindo is a printing company that is required to complete the production process on time with optimal print quality. High production targets, overtime, machine downtime, and sudden changes in work schedules have the potential to increase work pressure which impacts the high mental workload of production employees. This study aims to measure the level of mental workload of production employees using the NASA-TLX method. The analysis was carried out through weighting, rating, and calculating Weighted Workload (WWL). The results showed that all respondents had a very high level of mental workload with an average score above 80. The dominant factors influencing mental workload were Mental Demand (21%), followed by Own Performance (20%), Effort (18%), Temporal Demand (17%), Physical Demand (14%), and Frustration Level (9%). Therefore, the company is advised to conduct workforce evaluations, work schedule arrangements, improve training, and develop production facilities to reduce employee mental workload